2003
DOI: 10.1002/mus.10387
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar neuropathy in the forearm: A possible complication of diabetes mellitus

Abstract: Ulnar neuropathy in the forearm is an unusual cause of hand weakness and sensory loss that is most often attributed to compression of the nerve distally within the humero-ulnar arcade (cubital tunnel). An association with diabetes mellitus, however, has not been reported. We identified four patients with type I diabetes mellitus and clinical findings suggestive of ulnar neuropathy in whom electrophysiologic testing revealed partial conduction block or abnormal temporal dispersion within the forearm segment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…The abnormality in the superficial peroneal and sural nerves in the lower limb was more severe than in the median and ulnar nerve. The presence of conduction block and abnormal amplitude in our patients also raises the possibility that it was a manifestation of a more widespread demyelinating polyneuropathy, according to [23]. The correlation analysis showed that the nerve conduction block of lower limbs was more serious in the group of the increasement of uMMA/creatinine.…”
Section: Discussionsupporting
confidence: 61%
“…The abnormality in the superficial peroneal and sural nerves in the lower limb was more severe than in the median and ulnar nerve. The presence of conduction block and abnormal amplitude in our patients also raises the possibility that it was a manifestation of a more widespread demyelinating polyneuropathy, according to [23]. The correlation analysis showed that the nerve conduction block of lower limbs was more serious in the group of the increasement of uMMA/creatinine.…”
Section: Discussionsupporting
confidence: 61%
“…These results are in line with several previous studies on DM and CTS 15 16. Although the epidemiological data on UNE are scarce, and the number of large cohort studies on UNE is limited,17 the findings from this study corroborate both our previous work on identification of risk factors for CN4 and electrophysiological studies on UNE 3 18…”
Section: Discussionsupporting
confidence: 92%
“…An American Academy of Neurology subcommittee defined it as a Ͼ20% drop in CMAP amplitude with or without dispersion. 2 Very recent published studies continue to use this criterion, 1 and by using it, patients 1, 2, and 5 had partial conduction blocks in at least two motor nerves. Others argue that "probable" conduction block should be defined by a 40% drop.…”
Section: Discussionmentioning
confidence: 98%